Experimental study on the tribo-chemical smoothening process between self-mated silicon carbide in a water-lubricated surface-contact reciprocating test - Le Jin; Herbert Scheerer; Georg Andersohn; Matthias Oechsner; Dieter Hellmann (Friction)
Abstract Silicon carbide (SiC) can be tribo-chemically smoothened during a self-mated sliding procedure in the aqueous environment. As well reported in the point-contact tests, this smoothening process works well due to the abundant water as oxidant. After this smoothening process, the tribo-surface is well polished, a closely mated tribo-gap naturally forms, and an ultra-low friction state is built. However, water in the tribo-gap could be insufficient in industrial applications, e.g., the seal gap in mechanical seals. In this study, the tribo-chemical smoothening behavior in such environment was researched. A surface-contact reciprocating test was used to simulate the aqueous environment where water was insufficient. After tests, compared to the published results from the point-contact tests, the same ultra-low friction state was achieved. A part of the tribo-surface was tribo-chemically smoothened. The obtained smoothened surface microstructure was consistent with the published information. Meanwhile, severe abrasive wear occurred. A porous oxygen-rich layer was found existing beneath the abrasion-induced grooves, in which numerous smashed wear debris adhered on the worn surfaces. We concluded that the shortage of water initiated the severe abrasion, meanwhile the generated wear debris aggravated the wear condition. This understanding is instructive for developing new methods to avoid the severe abrasion in the same water insufficient environment.